2022
DOI: 10.1038/s41598-022-08845-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of fingernail samples as a biomarker for human exposure to arsenic-contaminated drinking waters

Abstract: This study evaluated the relationship between arsenic uptake via drinking water ingestion and arsenic concentration in fingernails as a biomarker for human exposure. For this purpose, we collected fingernail samples from 40 healthy participants of arsenic-affected rural regions of Kaboudrahang County, the west of Iran. A total of 49 fingernail samples were also collected from individuals who lived in areas where contamination of drinking water sources with arsenic had not been reported. It was found that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…After chronic ingestion of As, dermatologic lesions have been used as a long-term biomarker of cumulative arsenic exposure [56] (Hughes FM, 2006). A study investigating novel biomarker sampling methods found a significant association between groundwater and fingernail arsenic concentration [57].…”
Section: Arsenicmentioning
confidence: 99%
“…After chronic ingestion of As, dermatologic lesions have been used as a long-term biomarker of cumulative arsenic exposure [56] (Hughes FM, 2006). A study investigating novel biomarker sampling methods found a significant association between groundwater and fingernail arsenic concentration [57].…”
Section: Arsenicmentioning
confidence: 99%
“…In addition to the 40 healthy participants from the arsenic-affected rural areas of Iran, 49 fingernail samples were also collected from people who lived in areas where drinking water sources had not been reported to be contaminated with arsenic. It was found that the fingernail arsenic contents in 50 and 4.08% of the samples taken from arsenic-contaminated and reference villages were higher than the typical arsenic values of nails (0.43-1.08 g/g) [63]. The measurement of total arsenic in nails can be performed using the inductively coupled plasma-mass spectrometry (ICP-MS) technique [64].…”
Section: The Fate Of Arsenic: a Comprehensive Overview Of Its Biochem...mentioning
confidence: 99%